2016
DOI: 10.1016/j.icarus.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Titan’s evaporites

Abstract: Numerous geological features that could be evaporitic in origin have been identified on the surface of Titan. Although they seem to be water-ice poor, their main properties -chemical composition, thickness, stratification-are essentially unknown. In this paper, which follows on a previous one focusing on the surface composition (Cordier et al., 2013b), we provide some answers to these questions derived from a new model. This model, based on the up-to-date thermodynamic theory known as "PC-SAFT", has been valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 91 publications
2
44
0
Order By: Relevance
“…C 2 H 2 is highly soluble in Titan's liquid methane and ethane (Glein & Shock 2013;Cordier et al 2015;Singh et al 2015b), intermediate to the solubility of calcite and gypsum in water on Earth's surface. This property implies the existence dynamic surface processes: (1) erosion, through carving of fluvial channels and the formation of karstic lakes at high latitudes on Titan; (2) transport from the surface of continents after a rainstorm by surface runoff; and (3) sedimentation to the bottom of lakes and oceans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C 2 H 2 is highly soluble in Titan's liquid methane and ethane (Glein & Shock 2013;Cordier et al 2015;Singh et al 2015b), intermediate to the solubility of calcite and gypsum in water on Earth's surface. This property implies the existence dynamic surface processes: (1) erosion, through carving of fluvial channels and the formation of karstic lakes at high latitudes on Titan; (2) transport from the surface of continents after a rainstorm by surface runoff; and (3) sedimentation to the bottom of lakes and oceans.…”
Section: Discussionmentioning
confidence: 99%
“…It appears bright at all wavelengths and exceptionally bright at 5 μm, which has been interpreted as being due to enrichment in evaporite deposits (MacKenzie et al 2014). From thermodynamic calculations Cordier et al (2013Cordier et al ( , 2015 demonstrated that C 2 H 2 should be a major dissolved component in the lakes and should crystallize mainly in the upper part of evaporite deposits present in dried out depressions, possibly mixed with other organics such as butane due to the high solubility in Titan liquids.…”
Section: Distribution Of C 2 H 2 On Titanmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, I have checked that PC-SAFT reproduces the reference ternary mixture (N2, CH4, C2H6) of Gabis (1991) provided as supplementary data by Glein & Shock (2013). In the frame of this EoS, each considered species is characterized by the PC-SAFT three parameters, namely the segment diameter σ, the depth of the potential ǫ/kB, and the number of segments per chain m; the values of those parameters have all been given in Tan et al (2013);Cordier et al (2016). Beside this, the binary interaction parameters kij 's are also taken in this article.…”
Section: Estimation Of the Speed Of Sound In A Ternary Mixture Of Nitmentioning
confidence: 99%
“…Evaporites are also possible candidate materials for Titan sand (Barnes et al, 2015). Titan's evaporites may be made of acetylene, ethylene, or butane (Cordier et al, 2013(Cordier et al, , 2016Singh et al, 2017); however, these materials are not stable solids under room temperatures on Earth, and their solid mechanical properties also have not been measured under low temperatures.…”
Section: Introductionmentioning
confidence: 99%